Meloidogyne aegracyperi n. Sp. (Nematoda: Meloidogynidae), a root-knot nematode parasitizing yellow and purple nutsedge in New Mexico - Eisenback, J. D.; Holland, L. A.; Schroeder, J.; Thomas, S. H.; Beacham, J. M.; Hanson, S. F.; Paes-Takahashi, V. S. [UNESP]; Vieira, P. (De Gruyter, 2019)
Meloidogyne aegracyperi n. sp. is described from roots of purple nutsedge in southern New Mexico, USA. Mature females are small (310–460µm), pearly white, with their egg masses completely contained inside root galls. The neck is often at a 90 to 130° angle to the protruding posterior end with the perineal pattern. The distance of the dorsal esophageal gland orifice (DGO) to the base of the stylet is relatively long (4.0–6.1µm), and the excretory pore is level with the base of the stylet. The anterior portion of the rounded lumen lining of the metacorpus contains 3 to 10 small vesicles. The perineal pattern has a rounded dorsal arch with a tail terminal area that is smooth or marked with rope-like striae. Only two males were found. The body twists 90° throughout its length. The DGO to the base of the stylet is long (3.0–3.3) µm. The cephalic framework of the second-stage juvenile is weak, and the stylet is short (10.1–11.8µm). The DGO to the base of the stylet is long (3–5µm). The tail is very long (64–89µm) and the hyaline portion of the tail is very narrow, making the tail finely pointed. Eggs are typical for the genus and vary in length (85.2–99.8µm) and width (37.1–48.1µm), having a L/W ratio of (2.1–2.6). Maximum likelihood phylogenetic analyses of the different molecular loci (partial 18S rRNA, D2-D3 of 28S rRNA, internal transcribed spacer (ITS) rRNA, cytochrome oxidase subunit II (COII)-16S rRNA of mitochondrial DNA gene fragments and partial Hsp90 gene) placed this nematode on an independent branch in between M. graminicola and M. naasi and a cluster of species containing M. chitwoodi. M. fallax, and M. minor. Greenhouse tests showed that yellow and purple nutsedge were the best hosts, but perennial ryegrass, wheat, bentgrass, and barley were also hosts.
Keywords: C. esculentus; C. rotundus; Cyperus; Description; Host range; Morphology; Morphometrics; Scanning electron microscopy; Taxonomy